VD_FINDINFO Jug / 2009 / 10 vom 23. April 2009 - VD Tribunal cantonal (2009)
RETRAIT DE L'AUTORITÉ PARENTALE, CONVENTION{COMPÉTENCE DES AUTORITÉS EN MATIÈRE DE PROTECTION DES MINEURS} | 298a al. 2 CC, 311 al. 1 CC, 399a CPC, 85 al. 1 LDIP, 1 CLaH 61